EphrinA3 is a key regulator of malignant behaviors and a potential prognostic factor in lung adenocarcinoma. (30th June 2022) - Yiminniyaze, Ruzetuoheti; Zhang, Xiujuan; Zhu, Ning; Wang, Jing; Li, Chengwei; Wumaier, Gulinuer; Zhou, Daibing; Li, Jing; Xia, Jingwen; Zhang, Youzhi; Dong, Liang; Zhang, Yuanyuan; et al.
Abstract: Background: As a member of the Ephrin protein family that elicits short distance cell‐cell signaling, EphrinA3 has been shown to promote or inhibit tumorigenesis depending on tumor types, but its roles and the underlying mechanisms in lung adenocarcinoma (LUAD) have not been reported. Materials and Methods: The TCGA database and Kaplan‐Meier Plotter database were used to analyze the differential expression of EphrinA3 between LUAD and para‐carcinoma tissues, and its effect on overall survival of LUAD patients. CCK‐8 assay, Edu assay, and flow cytometry were used to probe the effect of EphrinA3 on the proliferation of LUAD cells, and transwell assay was employed to examine its effect on migration and invasion. In addition, the effect of EphrinA3 on the growth of LUAD was further evaluated using a xenograft tumor model. Results: EphrinA3 was expressed highly in LUAD, and its expression level was negatively correlated with the prognosis of LUAD patients. In addition, EphrinA3 promoted proliferation, migration, and invasion of LUAD cells, and accelerated tumor growth in a xenograft LUAD model. The reported EphrinA3 receptors, EphA1 and EphA10, were expressed in clinical LUAD tissues and co‐localized with EphrinA3 in LUAD cells. Mechanistically, EphrinA3/Eph signaling activated AKT, ERK, and p38MAPK, induced epithelial‐mesenchymal transition (EMT), and upregulated matrix metalloproteases‐2 and ‐9 (MMP‐2/−9). Conclusion: EphrinA3 expression was negatively correlated with prognosis of patients with LUAD. EphrinA3 promoted proliferation, migration, and invasion of LUAD cells. EphrinA3 enhanced the phosphorylation of ERK and AKT, and potentiates EMT and MMP expression in LUAD cells. Abstract : EphrinA3 expression was negatively correlated with prognosis of patients with LUAD. EphrinA3 promoted proliferation, migration and invasion of LUAD cells. EphrinA3 enhanced the phosphorylation of ERK and AKT, and potentiates EMT and MMP expression in LUAD cells.